Design and performance optimization of circularly polarized luminescent materials based on lanthanide helicates - Xiumei Zhang; Xinglu Wang; Wenru Huang; Sen Yin; Ting Gao; Yanyan Zhou; Hongfeng Li (Scientific Reports)
Abstract Chiral lanthanide complexes, due to their high luminescence dissymmetry factor (glum) and luminescent quantum yield, have become highly promising materials for circularly polarized luminescence (CPL). Herein, we report two novel pairs of lanthanide chiral complexes, which exhibit both a high glum and high luminescence quantum efficiency. Photophysical and chiroptical investigations revealed that both (NEt4)2[Eu2(L 1 S )4] and (NEt4)2[Eu2(L 2 S )4] displayed intense CPL. Their glum values for 5D0 → 7F1 transition reach + 1.34 and + 1.14, respectively, exhibiting high luminescence quantum yields of 37.43% and 30.30% for 5D0 → 7FJ transitions (J = 0 − 4). Through the analysis of the photophysical properties and X-ray single-crystal structures of (NEt4)2[Eu2(L 1 S )4] and (NEt4)2[Eu2(L 2 S )4], it was found that the modification of the ligand significantly affected the twist angle α of the coordination polyhedron, revealing the direct cause for achieving a high glum. This study provides a new design concept for the development of other lanthanide-based CPL materials with high glum values and high luminescence quantum yields.